Transcending history's heavy hand: The future in economic action - Jens Beckert; Timur Ergen (Max Planck Institute for the Study of Societies, 2020)
This paper discusses sociological analyses of the formation and role of expectations in the economy. Recognition of the social constitution of expectations advances the understanding of economic action under conditions of uncertainty and helps to explain core features of modern capitalist societies. The range of applications of the analytical perspective is illustrated by closer examination of three core spheres of capitalist societies: consumption, investment, and innovation. To provide an idea of core challenges of the approach, three major research questions for the sociological analysis of expectations are presented. – – Wie lassen sich die Entstehung und die Rolle von Erwartungen in der Wirtschaft soziologisch analysieren? Erwartungen sind sozial konstituiert. Der Rekurs auf Erwartungen trägt zum Verständnis wirtschaftlichen Handelns unter Bedingungen von Unsicherheit und zum Verständnis charakteristischer Wesenszüge moderner kapitalistischer Gesellschaften bei. Nähere Betrachtungen von drei Sphären wirtschaftlicher Aktivität - Konsum, Investition und Innovation - verdeutlichen das breite Spektrum möglicher Anwendungen der Erwartungsperspektive in der Wirtschaftssoziologie. Die zentralen Herausforderungen für die soziologische Analyse von Erwartungen werden anschließend anhand von drei wichtigen Forschungsfragen skizziert.
hdl:21.11116/0000-0005-E443-E
Keywords: 300; action theory; economic sociology; expectations; firms; innovation; markets; social change; Erwartungen; Handlungstheorie; Innovation; Märkte; Organisationen; sozialer Wandel; Wirtschaftssoziologie